Casein Kinases 2-dependent phosphorylation of the placental ligand VAR2CSA regulates Plasmodium falciparum-infected erythrocytes cytoadhesion. - Dominique Dorin-Semblat; Jean-Philippe Semblat; Romain Hamelin; Anand Srivastava; Marilou Tetard; Graziella Matesic; Christian Doerig; Benoit Gamain (PLoS Pathogens)
Placental malaria is characterized by the massive accumulation and sequestration of infected erythrocytes in the placental intervillous blood spaces, causing severe birth outcomes. The variant surface antigen VAR2CSA is associated with Plasmodium falciparum sequestration in the placenta via its capacity to adhere to chondroitin sulfate A. We have previously shown that the extracellular region of VAR2CSA is phosphorylated on several residues and that the phosphorylation enhances the adhesive properties of CSA-binding infected erythrocytes. Here, we aimed to identify the kinases mediating this phosphorylation. We report that Human and Plasmodium falciparum Casein Kinase 2α are involved in the phosphorylation of the extracellular region of VAR2CSA. We notably show that both CK2α can phosphorylate the extracellular region of recombinant and immunoprecipitated VAR2CSA. Mass spectrometry analysis of recombinant VAR2CSA phosphorylated by recombinant Human and P. falciparum CK2α combined with site-directed mutagenesis led to the identification of residue S1068 in VAR2CSA, which is phosphorylated by both enzymes and is associated with CSA binding. Furthermore, using CRISPR/Cas9 we generated a parasite line in which phosphoresidue S1068 was changed to alanine. This mutation strongly impairs infected erythrocytes adhesion by abolishing VAR2CSA translocation to the surface of infected erythrocytes. We also report that two specific CK2 inhibitors reduce infected erythrocytes adhesion to CSA and decrease the phosphorylation of the recombinant extracellular region of VAR2CSA using either infected erythrocytes lysates as a source of kinases or recombinant Human and P. falciparum casein kinase 2. Taken together, these results undoubtedly demonstrate that host and P. falciparum CK2α phosphorylate the extracellular region of VAR2CSA and that this post-translational modification is important for VAR2CSA trafficking and for infected erythrocytes adhesion to CSA.